Climate change and public health in Africa: A narrative review of resilience strategies for health systems - Kabiru Gulma; Sa’adatu M. Julde; Isman Wais; Emmanuel Morna; Abubakar S. Danbatta; Bakam Rodine; Anastacia Katungo Maluki (Public Health and Occupational Safety Journal, 2026)
Background: Climate change poses an escalating threat to public health in Africa, a continent responsible for less than 10% of global greenhouse gas emissions yet disproportionately bearing the burden of its consequences. Existing health systems remain fragile, under-resourced, and ill-equipped to absorb climate-related shocks. Objectives: To synthesize evidence on the health impacts of climate change in Africa and identify strategies for building climate-resilient health systems. Methods: This study is a narrative literature review. A comprehensive search of peer-reviewed databases and gray literature was conducted. Sources were screened against predefined inclusion criteria and synthesized thematically across six domains: climate science, contextual vulnerabilities, health systems strengthening, governance, community engagement, and financing. A total of 22 studies and reports were included and analyzed using thematic synthesis following Thomas and Harden’s (2008) three-step approach. Results: Climate change intensifies the burden of infectious and non-communicable diseases, disrupts health infrastructure, and deepens health inequities across African regions. Resilience-building requires strengthened governance, sustained domestic and international financing, multisectoral partnerships, community engagement, and climate-adaptive health information systems. Conclusions: Concerted, context-sensitive action that integrates climate adaptation into health policy frameworks is urgently needed to protect the health and well-being of African populations from the accelerating impacts of climate change. Practical implications include strengthening health system governance, mobilizing climate finance, investing in climate-adaptive surveillance systems, and fostering community engagement and multisectoral collaboration to build durable climate resilience across African health systems.